MATHEMATICAL MODELS OF PROCESSES AND SYSTEMS OF TECHNICAL OPERATION FOR ONBOARD COMPLEXES AND FUNCTIONAL SYSTEMS OF AVIONICS - S. V. Kuznetsov (Научный вестник МГТУ ГА)
Modern aircraft are equipped with complicated systems and complexes of avionics. Aircraft and its avionics technical operation process is observed as a process with changing of operation states. Mathematical models of avionics processes and systems of technical operation are represented as Markov chains, Markov and semi-Markov processes. The purpose is to develop the graph-models of avionics technical operation processes, describing their work in flight, as well as during maintenance on the ground in the various systems of technical operation. The graph-models of processes and systems of on-board complexes and functional avionics systems in flight are proposed. They are based on the state tables. The models are specified for the various technical operation systems: the system with control of the reliability level, the system with parameters control and the system with resource control. The events, which cause the avionics complexes and functional systems change their technical state, are failures and faults of built-in test equipment. Avionics system of technical operation with reliability level control is applicable for objects with constant or slowly varying in time failure rate. Avionics system of technical operation with resource control is mainly used for objects with increasing over time failure rate. Avionics system of technical operation with parameters control is used for objects with increasing over time failure rate and with generalized parameters, which can provide forecasting and assign the borders of before-fail technical states. The proposed formal graphical approach avionics complexes and systems models designing is the basis for models and complex systems and facilities construction, both for a single aircraft and for an airline aircraft fleet, or even for the entire aircraft fleet of some specific type. The ultimate graph-models for avionics in various systems of technical operation permit the beginning of analytical models designing.